Evaluation of Delorme’s Procedure in the Treatment of Complete Rectal Prolapse- A Comparison with Abdominal Rectopexy (Well’s procedure) - Suman, Md Ariful Alam; Sarkar, Md Habibullah; Ahmed, Istiak; Abedin, Sulatanul; Islam, Md Shohidul; Islam, Syeda Nafisa (TAJ: Journal of Teachers Association, 2021)
Background: There are versatile operative techniques for treating complete rectal prolapse. Every procedure has some advantages and disadvantages. Delorme’s procedure and abdominal rectopexy (Well’s procedure) have gained more popularity. But to determine which approach is better, it is needed to evaluate the functional outcome of both procedures. Objective: To compare the outcome of Delorme’s procedure and abdominal rectopexy to treat complete rectal prolapse. Methodology: A randomized control trial was conducted in 25 patients with complete rectal prolapse in the department of Surgery, RMCH. They were divided into two groups by randomization. Fifteen patients included in Group-I underwent Delorme’s procedure, and ten patients included in group-II underwent abdominal rectopexy (Well’s procedure). The outcome of both procedures was compared postoperatively. Results: In group-1, we have found uneventful outcomes of 10 (66.66%) patients, and hemorrhage, minor incontinence, and retention of urine were found in 2(13.3%), 1(6.66), and 4(26.66%) patients, respectively. In group-2 patients, 5(50%) patients recovered uneventfully, whereas hemorrhage, surgical site infection, retention of urine, bladder dysfunction, and constipation were found in 2(20%), 1(10%), 1(10%), 1(10%) and 2(20%) patients respectively. The mean operation time in group-I was 92.86 min and in Group 2 was 124.00 min with a p-value of 0.001. The average post-operative hospital stay after Delorme’s procedure was <4 days in 4 patients and 4-6 days in the rest 11 patients. But the hospital stay is a little lengthier in the case of abdominal rectopexy (Well’s procedure), where seven patients were discharged within 4-6 days, and three patients were discharged after the 5th day of operation. In group I, expenditure was <7000 taka in 10 (66.66%) patients, whereas in group-2 , the cost was 10000-15000 in 7(70%) patients with a p-value of 0.001. Conclusion: We can conclude that Delorme’s procedure is comparatively safer and cost-effective than Well’s procedure, considering different vital parameters. TAJ 2021; 34: No-1: 40-46